Factors Influencing Consumer Purchase Intention in Syar’i Hijabs: Insights in Indonesia’s Halal Fashion Market - Nela Rizlah; Atiyah Fitri; Aslam Mei Nur Widigdo (Research Synergy Foundation, 2025)
The world's largest Muslim population is in Indonesia, although Muslim fashion buyers have not kept up with the opportunities that have arisen. The purpose of this study is to ascertain how consumer interest in purchasing syar'i hijab is influenced by pricing, product quality, and promotion. The study used a quantitative approach to causal relationships. The sampling technique used is probability sampling. The study's population consisted of Indonesian syar'i hijab wearers. A sample of 496 respondents representing 34 provinces in Indonesia. Online questionnaires were distributed to collect data. Data processing using SEM with SmartPLS software version 3.0. The results showed that price, promotion, and product quality partially had a significant positive effect on consumer purchase intention in the syar'i hijab. The implication of research for business actors, both hijab producers, and traders, is the need to maintain the quality of syar'i hijab, especially related to the innovation of syar'i hijab products that close perfectly but remain fashionable, as well as increase promotion through advertisements in various media.